Taking account of service externalities when spectrum is allocated and assigned. Issue 10 (October 2016) - Cave, Martin; Pratt, Neil
Abstract: Spectrum should be allocated among the various services which use it to maximise the aggregate incremental value (private and external) of those services minus the (non-spectrum) costs of supply. The external value of services such as broadcasting and mobile communications may be significant, yet we know that spectrum assignment by auction, for example, does not take them into account, because the successful bidder cannot monetise the value of the externality. The paper considers how this issue can be addressed. It notes that, if the spectrum assignment in question has no impact on the output of the services competing for it, value generated is unchanged, and the spectrum allocation problem reduces to the minimisation of the aggregate cost of non-spectrum inputs for the relevant services. In the more common case of variable outputs, some means of valuing external effects is needed, and possible approaches to valuation are discussed. Highlights: Discusses the problem of incorporating externalities in auction for spectrum. Identifies cases where valuation of such externalities is and is not required. Notes measurement issues involved and discusses how they can be overcome.